A Temperate Province? Evidence from Lower Canadian General Store Account Books, 1830-1857 - Craig, Béatrice (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2017)
Alcoholic consumption was unproblematic and supposedly widespread in the Canadas in the early years of the nineteenth century, until temperance movements sought to eradicate it through moral suasion, shaming and regulations in the second quarter of the century. In Lower Canada, the 1849-1850 temperance crusade spearheaded by father Chiniquy, with the support of religious and lay authorities would have led to a rapid collapse in the importation, production and sale of alcohol and the closing of numerous taverns. Evidence from country general store account books suggest that Lower Canadians were already moderate drinkers at the beginning of the century and that their consumption was already declining before Chiniquy launched his crusade, and his success would have been due to minds already half made. On the other hand, the availability of other stimulant beverages, such as coffee or tea does not seem to have played a role.